2017
DOI: 10.1093/rpd/ncx245
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Analytical Models of Stray Radiation Exposures From Photon- And Proton-Beam Radiotherapies

Abstract: External-beam radiation therapy is safe, effective and widely used to treat cancer. With 5-year cancer survival for adults above 70%, increasingly research is focusing on quantifying and reducing treatment-related morbidity. Reducing exposures to healthy tissues is one strategy, which can be accomplished with advanced-technology radiotherapies, such as intensity-modulated photon therapy and proton therapy. Both of these modalities provide good conformation of the therapeutic dose to the tumor volume, but they … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…Specifically, stray radiation exposure is typically underestimated beyond a few centimeters outside the treatment field, precluding routine risk projections based on radiation exposure. 42 Similarly, their risk-modeling capabilities are limited, if they are present at all. 43,44…”
Section: Clinical Presentations and Applications Of Proton Beam Therapymentioning
confidence: 99%
“…Specifically, stray radiation exposure is typically underestimated beyond a few centimeters outside the treatment field, precluding routine risk projections based on radiation exposure. 42 Similarly, their risk-modeling capabilities are limited, if they are present at all. 43,44…”
Section: Clinical Presentations and Applications Of Proton Beam Therapymentioning
confidence: 99%
“…Despite strong evidence of the importance of stray radiation to patient outcomes, commercial treatment planning systems (TPSs) significantly underestimate the total absorbed dose outside of the therapeutic treatment field . Figure shows a representative example of this underestimation.…”
Section: Introductionmentioning
confidence: 99%
“…This has led to the emergence of numerous alternative methods for quantifying out‐of‐field doses from photon radiotherapy including measurements, Monte Carlo simulations, and analytical models . Of these, measurements are considered the gold standard in terms of accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…77,78 New models and algorithms for such calculations are being developed. [79][80][81] Importantly, the prospective adoption of such capabilities at only a few major cancer centers would dramatically accelerate collection of the high-quality dosimetry data that is needed to improve current radiation risk models.…”
Section: Normal Tissue Damage Modelsbiological and Mathematicalmentioning
confidence: 99%
“…Prior to the early 2010's, one could reasonably argue that the lack of this capability was justified by a combination of factors: modeling radiation exposures was difficult; stray exposures are deemed clinically insignificant; and the uncertainties in predicted outcomes are excessive. However, since that time, the ability to routinely assess exposures has become eminently more feasible for advanced technology radiotherapies, 80 including proton-and photon-beam treatments and, indeed, has been implemented in non-clinical treatment planning systems. Although the uncertainties in predicting risks of a late effect for an individual patient remain relatively large, especially when the exposure includes neutrons, several studies now have shown that these uncertainties are manageable for comparing risks to the same patient from multiple candidate treatments.…”
Section: Normal Tissue Damage Modelsbiological and Mathematicalmentioning
confidence: 99%